2021
DOI: 10.1182/blood.2020008551
|View full text |Cite
|
Sign up to set email alerts
|

Very long chain fatty acid metabolism is required in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) cells have an atypical metabolic phenotype characterized by increased mitochondrial mass as well as a greater reliance on oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) for survival. To exploit this altered metabolism, we assessed publicly available databases to identify FAO enzyme overexpression. VLCAD (ACADVL) was found to be overexpressed and critical to leukemia cell mitochondrial metabolism. Genetic attenuation or pharmacological inhibition of VLCAD hindered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 121 publications
(403 reference statements)
4
38
0
Order By: Relevance
“…Interestingly, a recent study showed that LSCs derived from relapsed AML patients can increase fatty acid metabolism to compensate for OXPHOS impairment 27 , thus suggesting that fatty acid metabolism is also important for AML survival. This is also supported by recent findings, highlighting the importance of fatty acid metabolism in AML mitochondrial metabolism, and the potential to inhibit this metabolic vulnerability as a novel therapeutic approach 29 . Finally, AML blasts with high ROS levels in contrast to LSCs (ROS-low) are dependent on glycolysis to produce energy 27 , and this observation is considered to be very critical, because it demonstrates that heterogeneity within the leukemic clone is crucial in leukemogenesis.…”
Section: Leukemic Stem Cells and Metabolismsupporting
confidence: 68%
“…Interestingly, a recent study showed that LSCs derived from relapsed AML patients can increase fatty acid metabolism to compensate for OXPHOS impairment 27 , thus suggesting that fatty acid metabolism is also important for AML survival. This is also supported by recent findings, highlighting the importance of fatty acid metabolism in AML mitochondrial metabolism, and the potential to inhibit this metabolic vulnerability as a novel therapeutic approach 29 . Finally, AML blasts with high ROS levels in contrast to LSCs (ROS-low) are dependent on glycolysis to produce energy 27 , and this observation is considered to be very critical, because it demonstrates that heterogeneity within the leukemic clone is crucial in leukemogenesis.…”
Section: Leukemic Stem Cells and Metabolismsupporting
confidence: 68%
“…86 AML cells rely on fatty acids along with other essential energy sources for their metabolic needs. FAO was recently shown to be essential for leukemic cells in AML, 87 for which, notably, fructose metabolism, as depicted in Figure 1, would be directly supportive.…”
Section: Fatty Acid Metabolism In Amlmentioning
confidence: 82%
“…In addition to DNA replication, cell cycle regulation, and proliferation-related gene sets, which are likely secondary to DNA damage after cytarabine, our gene expression studies uncovered signatures of deregulated cell adhesion, proteostasis, as well as repressed OXPHOS and fatty acid metabolism, and RNA splicing, all of which are critical for hematopoietic stem cell function and are commonly deregulated during aging and in myeloid malignancies. Notably, deregulation of ribosome biogenesis and protein degradation may reflect loss of stemness 84,85 , whereas increased reliance on OXPHOS and fatty acid metabolism are characteristic of chemoresistant acute myeloid leukemia 49,52,86 and together with altered splicing engender potential therapeutic vulnerabilities 50,87,88 . It will be interesting to investigate if these processes contribute to the leukemic progression in individuals with clonal hematopoiesis with DNMT3A mutations [89][90][91][92][93][94] to serve as biomarkers for high risk of AML development.…”
Section: Discussionmentioning
confidence: 99%